Explaining the National Propensity to Expropriate: An Ecological Approach - Knudsen, Harald (Journal of International Business Studies, 1974)
Theories from several disciplines are integrated into a general model for the prediction of a national propensity to expropriate foreign private direct investments in less-developed host countries. A discriminant analysis is used to test the hypothesis that the presence of such instability combined with a high level of foreign (American) investments will result in a high propensity to expropriate. The model is tested empirically on Latin American data from the 1968–71 period, and the main hypothesis confirmed.